Perspectives of system informatics : 10th International Andrei Ershov Informatics Conference, PSI 2015, in Memory of Helmut Veith, Kazan and Innopolis, Russia, August 24-27, 2015, Revised selected papers /: 10th International Andrei Ershov Informatics Conference, PSI 2015, in Memory of Helmut Veith, Kazan and Innopolis, Russia, August 24-27, 2015, Revised selected papers. (2016) - Unknown
No abstract available